Dinâmica do carbono durante a decomposição de palha de trigo marcada com 13C e dejetos líquidos de suínos - Luz, Laura Patrícia da (2007)
In no-tillage areas, the pig slurry is applied on the cultural residues, as much as cover or commercial crops. A few research information exists involving the soil carbon dynamics with this modality of pig slurry application. A better understanding of soil carbon dynamics during the decomposition of pig slurry and cultural residues is necessary, as much of the environmental point of view as of the maintenance and improvement of soil quality. This work was carried out in laboratory conditions, with the objective of evaluating the dynamics of the carbon during the decomposition of 13C-labelled wheat straw and pig slurry, used separately or mixed, with and without soil incorporation. In a Hapludalf soil and using an entirely randomized design were evaluated the following treatments, with four replications: T1 - Soil; T2 - Soil + straw in surface; T3 - Soil + incorporated straw; T4 - Soil + pig slurry in surface; T5 - Soil + pig slurry incorporated; T6 - Soil + pig slurry incorporated + straw in surface; T7 - Soil + pig slurry incorporated + incorporated straw; T8 - Soil + straw in surface + pig slurry in surface. The soil humidity was adjusted for 100% of the field capacity and the incubation was carried out for 95 days with temperature kept in 25ºC. The C-CO2 evolution and its isotopic 13C excess were evaluated continually and, periodically, the amounts of remaining C straw and C soil, with their respective 13C isotopic excess. The apparent C mineralization of pig slurry didn't increased with its soil incorporation, which just favored the straw C mineralization. In the treatments with wheat straw, with and without pig slurry, the apparent C mineralization (C-CO2) of straw in 95 days was, on average, of 58,4%, while the real C straw mineralization (13C-CO2) was of 45,8%, evidencing the occurrence of positive "priming effect." Despite of the high C/N (65,2) of wheat straw, its C mineralization just increased when was maintained in soil surface and the pig slurry were applied on the straw. In this condition, where the contact of straw with the soil is deficient, the presence of N mineral of pig slurry favored the heterotrophic microbial population, responsible for straw decomposition. With the higher contact of the straw with the soil, for its incorporation, the microorganisms supplied their N needs for biosynthesis from straw and soil organic matter mineralization, independently of N from pig slurry application. At the end of the experiment, the balance of 13C (13C-straw + 13C-soil + 13C-CO2), indicated that, in the average of all treatments, about 24% of the applied 13C with the straw were not recovered, probably for the incomplete capture of the 13C-CO2 liberated and for the difficulty in recovering the straw completely, in the treatments in that it was incorporated to the soil